Antimicrobial Study of Chloroform Fraction from the Leaves of Entada spiralis Ridl. - Fitri Rachmadita; Erryana Martati; Sharifah Nurul Akilah Syed Mohamad; Siti Zaiton Mat So'ad (IIUM Press, International Islamic University Malaysia, 2021)
Introduction: Entada Spiralis Ridl., or locally identified as Sintok, contains flavonoid, saponin, tannin, and glycoside, compounds that have antifungal and antibacterial activities. This research aims to identify bioactive compounds and determine the antimicrobial activity from crude and fraction of E. spiralis extract. Methods: The crude extract was prepared by macerating the leaves with chloroform, and then proceeded to fraction it by vacuum liquid chromatography with Dichloromethane (DCM)/Hexane (Hex) (1/9) and Dichloromethane (DCM)/Methanol (MeOH) (9/1) solvent system. Disk Diffusion Test and Microdilution Assay evaluated the extracts' antimicrobial activity against S. aureus, E. coli and C. albicans. The determination of bioactive compounds was done by Thin Layer Chromatography (TLC). Determination of Total Phenolic (TPC) and Flavonoid Content (TFC) were performed by Folin-Ciocalteu and AlCl3 Colourimetric Assay Results: The greatest inhibition zone against C. albicans was obtained from fraction Chloroform (CHCl3) extract with an inhibition zone of 10.33 mm. DCM/MeOH (9/1) effectively killed S. aureus and E.coli with an inhibition zone of 11.67 and 12 mm, respectively. The minimum inhibitory concentration (MIC) of CHCl3 crude extract were 1.563 mg/mL for both E. coli and S. aureus, and 0.781 mg/mL for C. albicans. The TLC revealed the presence of tannins, saponin, glycosides, phenol, flavonoid, triterpenoid, and aromatic compound in CHCl3 crude extract. TPC of DCM/MeOH (9/1), CHCl3, and DCM/Hex (1/9) were 50.56 ± 0.188, 51.913± 0.089, 24.16 ± 0.175 mg GAE/g extract. Conclusion: In conclusion, E. spiralis leaves could be a source of active antifungal and antimicrobial agents used for food preservation by using a semipolar solvent for extraction.